Incidence, prognosis, and perinatal outcomes of and risk factors for severe twin-twin transfusion syndrome with right ventricular outflow tract obstruction in the recipient twin after fetoscopic laser photocoagulation - Yao-Lung Chang; An-Shine Chao; Shuenn-Dyh Chang; Po-Jen Cheng; Wen-Fang Li; Chin-Chieh Hsu (BMC, 2022)
Abstract Background Right ventricular outflow tract obstruction (RVOTO) is the most frequently encountered congenital heart disease in patients with twin -twin transfusion syndrome (TTTS) and is especially prevalent in the recipient twin. In this retrospective study, we evaluated the incidence, prognosis, postnatal management, and perinatal outcomes of and risk factors for RVOTO in the recipient twin in severe TTTS cases which diagnosed before 26 weeks after fetoscopic laser photocoagulation (FLP) at a single center in Taiwan. Methods RVOTO was diagnosed using fetal or postnatal echocardiography. The fetal outcomes evaluated were perinatal survival rate, neonatal brain image anomalies rate, gestational age at delivery, and birth weight. Results Total 187 severe TTTS cases were included; 14 (7.49%) had a recipient twin with RVOTO (12 cases of pulmonary stenosis and 2 of pulmonary atresia). Of these 14 cases, 3 (21.4%) demonstrated improvements in outflow obstruction after FLP, and 11 (78.6%) resulted in perinatal survival. Of the 11 survivors, 5 (45.5%) received transcatheter balloon valvuloplasty to alleviate the RVOTO. The perinatal survival rate, gestational age at delivery, neonatal brain image anomaly rate, and birth weights did not significantly differ between the groups in which the recipient twin had versus did not have RVOTO. Generally, the recipient twin had RVOTO received FLP at a younger gestational age (in weeks; 19.3 ± 2.4 vs. 20.7 ± 2.6, p = 0.048) and had a higher percentage of cases at Quintero stage IV (50.0% vs. 12.1%, p < 0.001) than those in which the recipient twin did not have with RVOTO. Using logistic regression, we discovered that FLP at a younger gestational age (p = 0.046, odds ratio = 0.779) and TTTS at Quintero stage IV (p = 0.001, odds ratio = 7.206) were risk factors for the recipient twin developing RVOTO after FLP in severe TTTS cases. Conclusions The post-FLP perinatal outcomes of cases of severe TTTS in which the recipient twin had versus did not have RVOTO were comparable in this study, which may have been due to the similar gestational ages at delivery and strong influence of high Quintero stages (stages III and IV).